2022
DOI: 10.1038/s41598-022-13557-8
|View full text |Cite
|
Sign up to set email alerts
|

Deletion in chromosome 6 spanning alpha-synuclein and multimerin1 loci in the Rab27a/b double knockout mouse

Abstract: We report an incidental 358.5 kb deletion spanning the region encoding for alpha-synuclein (αsyn) and multimerin1 (Mmrn1) in the Rab27a/Rab27b double knockout (DKO) mouse line previously developed by Tolmachova and colleagues in 2007. Western blot and RT-PCR studies revealed lack of αsyn expression at either the mRNA or protein level in Rab27a/b DKO mice. PCR of genomic DNA from Rab27a/b DKO mice demonstrated at least partial deletion of the Snca locus using primers targeted to exon 4 and exon 6. Most genes lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…We generated Rab27b single KO mice after crossing Rab27a/Rab27b double KO (DKO) mice obtained from Dr. Seabra [34] with wildtype (WT) C57BL/6J mice. Of note, we previously found that the Rab27a/b DKO mouse carries a spontaneous deletion that includes Snca , the gene that encodes αsyn, and Mmrn1 , the gene that encodes multimerin 1 [35]. This deleted region on chromosome 6 was restored in a subset of progeny after crossing the DKO mice with C57BL/6J mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We generated Rab27b single KO mice after crossing Rab27a/Rab27b double KO (DKO) mice obtained from Dr. Seabra [34] with wildtype (WT) C57BL/6J mice. Of note, we previously found that the Rab27a/b DKO mouse carries a spontaneous deletion that includes Snca , the gene that encodes αsyn, and Mmrn1 , the gene that encodes multimerin 1 [35]. This deleted region on chromosome 6 was restored in a subset of progeny after crossing the DKO mice with C57BL/6J mice.…”
Section: Resultsmentioning
confidence: 99%
“…For maintenance breeding, Rab27b +/- heterozygous mice were bred together to generate litters with both WT control (Rab27b +/+ ) and Rab27b-KO (Rab27b -/- ) pups for experimental use. Mice were genotyped for Rab27b and αsyn Exon 4 as previously described [35].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation